Triode Solid Oxide Fuel Cell Operation Under Sulfur‐Poisoning Conditions1. Issue 4 (27th April 2017) - Caliandro, P.; Diethelm, S.; Van herle, J.
Abstract: The triode solid oxide fuel cell (SOFC) is a three electrodes configuration. The third electrode, so‐called auxiliary, is connected in a way to run in electrolysis mode, while cathode and anode operate in normal fuel cell mode. This mixed operation allows to reach anode–cathode potential differences which are not accessible in normal operation. In this work, the benefits of triode operation under sulfur‐poisoning conditions are shown. In particular, the difference between conventional and triode operation mode under 2ppm of H2 S in H2 are analyzed. The partial reversibility of sulfur poisoning is investigated and the observed regeneration processes are discussed for both the conventional and triode operation. After each sequence of exposure and regeneration, IV and EIS characteristics are taken. The electrochemical impedance spectra are further processed by computing the distribution of relaxation times (DRT). During triode operation, less degradation during exposure and faster stabilization after exposure and regeneration with respect to conventional operation mode are observed.